Determinan Kualitas Laba pada Perbankan Syariah: Pengaruh Struktur Modal dan Likuiditas Periode 2021–2024 - Gustika Nurmalia; Bagas Herdi Prasetio; Muhamad Iqbal; Endang Marlina (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2026)
This study aims to analyze the effect of Debt to Equity Ratio (DER) and Financing to Deposit Ratio (FDR) on Quality of Earnings (QoE) in Islamic banking. The study employs a quantitative approach using secondary data analyzed through panel data regression with the assistance of EViews software. The results indicate that, partially, DER has a negative but insignificant effect on Quality of Earnings (QoE), with a probability value of 0.2320 (>0.05) and a coefficient of -0.005391. Meanwhile, FDR has a positive and significant effect on Quality of Earnings (QoE), with a probability value of 0.0226 (<0.05) and a coefficient of 0.054601. Simultaneously, DER and FDR have a significant effect on Quality of Earnings (QoE), as indicated by the Prob. F-statistic value of 0.005474 (<0.05). The Adjusted R-squared value of 0.262013 indicates that DER and FDR are able to explain 26.2013% of the variation in Quality of Earnings (QoE), while the remaining 73.7987% is explained by other factors outside the research model. Based on these findings, it can be concluded that only Financing to Deposit Ratio (FDR) has a significant effect on Quality of Earnings (QoE), whereas Debt to Equity Ratio (DER) does not have a significant effect. Penelitian ini bertujuan untuk menganalisis pengaruh Debt to Equity Ratio (DER) dan Financing to Deposit Ratio (FDR) terhadap Quality of Earnings (QoE) pada perbankan syariah. Penelitian menggunakan pendekatan kuantitatif dengan data sekunder yang dianalisis menggunakan regresi data panel melalui aplikasi EViews. Hasil penelitian menunjukkan bahwa secara parsial DER berpengaruh negatif namun tidak signifikan terhadap Quality of Earnings (QoE) dengan nilai probabilitas sebesar 0,2320 (>0,05) dan koefisien sebesar -0,005391. Sementara itu, FDR berpengaruh positif dan signifikan terhadap Quality of Earnings (QoE) dengan nilai probabilitas sebesar 0,0226 (<0,05) dan koefisien sebesar 0,054601. Secara simultan, DER dan FDR berpengaruh signifikan terhadap Quality of Earnings (QoE), yang ditunjukkan oleh nilai Prob. F-statistic sebesar 0,005474 (<0,05). Nilai Adjusted R-squared sebesar 0,262013 menunjukkan bahwa DER dan FDR mampu menjelaskan variasi Quality of Earnings (QoE) sebesar 26,2013%, sedangkan sisanya sebesar 73,7987% dijelaskan oleh faktor lain di luar model penelitian. Berdasarkan hasil penelitian dapat disimpulkan bahwa hanya Financing to Deposit Ratio (FDR) yang terbukti berpengaruh signifikan terhadap Quality of Earnings (QoE), sedangkan Debt to Equity Ratio (DER) tidak memiliki pengaruh yang signifikan.